Institutional self-deception - Jacot-Guillarmod, Genevieve Nicole (Rhodes University, Faculty of Humanities, Department of Philosophy)
There are many examples of institutions which have made false claims, or performed certain acts, that have had, to varying degrees, a negative impact on their societies. For example, many corporations go to great lengths to present themselves as being environmentally friendly when in fact they are not. Many corporations have also been forced to recall dangerous products which they at one time or another insisted were safe. Research teams have misled participants with regard to what they can expect from their participation in studies, with grave consequences. Governments throughout the world are mired in corruption, and yet deny that this is so. One possible explanation is that in such situations these institutions are simply lying. However, another possible explanation is that these institutions are self-deceived, or lying to themselves. Recently it has been suggested that self-deception is something that affects certain groups as well as individuals. Given that institutions can wield a great deal of political, social and economic power, if institutions are capable of self-deception there is room for things to go awry on a very large scale with potentially dire consequences. Yet the explanations currently on offer for group-level self-deception appear to amount to instances of individual self-deception (either to certain key individual members of those groups being self-deceived, or to all or most members of a group sharing the same self-deceptive belief), and as such I do not regard the explanations currently on offer as satisfactory. I propose that there are certain situations in which we ought to see institutions themselves as self-deceived or lying to themselves. While the terms 'self-deception' and 'lying to oneself' are often used interchangeably, I differentiate between the two and argue that both institutional self-deception and an institution lying to itself are institution-level phenomena, and do not rely on any individual within the institution being self-deceived or lying to themselves. That this is so is of relevance to our attributions of accountability, and makes changes to institutional structure and procedures the focus of concern when it comes to preventing an institution succumbing to self-deception or lying to itself.
Keywords: Self-deception; Business ethics; Social responsibility of business; Responsibility; Collective behavior -- Moral and ethical aspects; Attribution (Social psychology)